2021
DOI: 10.1002/bco2.100
|View full text |Cite
|
Sign up to set email alerts
|

Nurse‐led one stop hematuria clinic: Outcomes from 2,714 patients

Abstract: Objectives Objective of this study is to report the results of nurse led hematuria clinic service outcome of 2,714 patients. Subjects and methods We conducted a retrospective, single center review of 2714 patients with visible and nonvisible hematuria managed by a well‐trained nurse specialist in a rapid access clinic (RAC) between 2014 and 2020. All patients received a full review, flexible cystoscopy performed by a nurse, and ultrasound of urinary tracts. After investigations, patients were reassured and dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 29 publications
(60 reference statements)
0
10
0
Order By: Relevance
“…In total, 65 studies were included in this review [20–84] (Table S1), and divided in two categories; (A) studies describing clearly how many of men referred to hospital or private practice for evaluation of haematuria aetiology had prostate cancer ( n = 42) [20–61], and (B) studies clearly describing haematuria as a presenting symptom leading to a prostate cancer diagnosis ( n = 23) [62–84]. The 42 studies describing evaluation of haematuria were included in a meta‐analysis [20–61]. All of the 42 studies […”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In total, 65 studies were included in this review [20–84] (Table S1), and divided in two categories; (A) studies describing clearly how many of men referred to hospital or private practice for evaluation of haematuria aetiology had prostate cancer ( n = 42) [20–61], and (B) studies clearly describing haematuria as a presenting symptom leading to a prostate cancer diagnosis ( n = 23) [62–84]. The 42 studies describing evaluation of haematuria were included in a meta‐analysis [20–61]. All of the 42 studies […”
Section: Resultsmentioning
confidence: 99%
“…Almost all included studies reported performing either cystoscopy or imaging, or both, but as a DRE and PSA test are the initial clinical tests for the evaluation of prostate cancer, we enumerated the prostate cancer prevalence for studies that clearly described performing a DRE or PSA test on all included men (n = 11) [21][22][23][24]26,29,32,33,38,44,58]. In these 11 studies, the pooled prevalence (95% CI) of prostate cancer was 3.1% (1.9-4.5%; Fig.…”
Section: Diagnostic Approach For Prostate Cancermentioning
confidence: 99%
See 2 more Smart Citations
“…Interestingly, they were not able to show improved diagnostic performance when adding MRI to the ERSPC risk calculator. Stone et al 4 looked at the transperineal prostate biopsy method as a way to evaluate men with an abnormal MRI who might consider focal therapy. In this series, the transperineal was more of a saturation method and was positive in 53% for clinically significant disease.…”
mentioning
confidence: 99%